2014
DOI: 10.1039/c4fd00046c
|View full text |Cite
|
Sign up to set email alerts
|

Electro-deposition and re-oxidation of carbon in carbonate-containing molten salts

Abstract: The electrochemical deposition and re-oxidation of solid carbon were studied in CO3(2-) ion-containing molten salts (e.g. CaCl2-CaCO3-LiCl-KCl and Li2CO3-K2CO3) at temperatures between 500 and 800 °C under Ar, CO2 or N2-CO2 atmospheres. The electrode reactions were investigated by thermodynamic analysis, cyclic voltammetry and chronopotentiometry in a three-electrode cell under various conditions. The findings suggest that the electro-reduction of CO3(2-) is dominated by carbon deposition on all three tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 14 publications
0
81
0
Order By: Relevance
“…355 More importantly, it was confirmed that Li + ions play an essential role for carbon electro-deposition in carbonate-only electrolytes. 355,356 Electrochemical oxidation of the deposited carbon was also investigated, 355 and preliminary findings, as shown in Fig. 41, indicate two plateaux on the potential-time profiles related to the anodic oxidation of the deposited carbon.…”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 73%
See 3 more Smart Citations
“…355 More importantly, it was confirmed that Li + ions play an essential role for carbon electro-deposition in carbonate-only electrolytes. 355,356 Electrochemical oxidation of the deposited carbon was also investigated, 355 and preliminary findings, as shown in Fig. 41, indicate two plateaux on the potential-time profiles related to the anodic oxidation of the deposited carbon.…”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 73%
“…graphite rod. 355 Although there are many similarities between DCFCs and MCFCs, the DCFC is the only type of fuel cell that uses a solid fuel (i.e., various forms of solid carbon) instead of using gaseous fuels, such as hydrogen gas and coal gas. Another distinctive characteristic of the DCFC is the fixed chemical potentials of both reactant (carbon) and the product (carbon dioxide), which are irrelevant to the fuel conversion rate or position within the cell.…”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 This method relies on the decomposition of dissolved CO 2 between two biased electrodes, where elemental carbon is captured at the cathode, and the resulting structures of the deposited carbons are largely dependent on process parameters including electrolyte, current density, and electrode materials. [9][10][11][12][13][14][15][16] The equations that govern this process are:…”
mentioning
confidence: 99%